ANALYSIS OF REGIONAL SUPERIOR PRODUCT STUDY OF PENUKAL ABAB LEMATANG ILIR DISTRICT, SOUTH SUMATERA - Simanjuntak, Megawati; Aprilia, Nurazizah; Salsabila, Farhah Azizah; Rossalia, Deasy; Rumbiati, Rumbiati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to identify and evaluate the superior regional products of Penukal Abab Lematang Ilir (PALI) Regency, South Sumatera, using the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The primary problem addressed is the need for a structured approach to prioritize regional products based on key criteria. The study evaluates five products: Sagarurung, Jengkol Chips, Aluminum Crafts, Bumi Ayu Temple, and Batik PALI, across criteria including economic contribution, price, market potential, socio-cultural value, and product uniqueness. The AHP method was used to determine the weight of each criterion, revealing that economic contribution was the most significant (0.262), followed by price (0.236). The TOPSIS method then ranked Sagarurung as the highest-performing product with a preference value of 0.823, indicating its strong economic impact and market potential. Batik PALI followed with a preference value of 0.551, excelling in uniqueness and socio-cultural value. The results suggest that while Sagarurung and Batik PALI are the leading products, others like Aluminum Crafts, Jengkol Chips, and Bumi Ayu Temple require targeted improvements to enhance their competitiveness. The study concludes by recommending focused strategies to optimize the development of these products, leveraging their strengths and addressing identified weaknesses.